Intentions And Behavior Of Partner Palm Oil Farmers PT Hari Sawit Jaya On Sustainable Palm Oil Management - Siahaan, Herlyna Novasari; Waluyati, Lestari; Masyhuri, Masyhuri (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
Sustainable palm oil management needs to be supported by all oil palm actors, both smallholders and oil palm plantation companies. PT Hari Sawit Jaya through the created share value program empowers independent smallholders around the company to become partner farmers to support a sustainable palm oil program. The present study aimed (1) to find out the factors that influence the intention of farmers to carry out sustainable palm oil management and (2) to determine the effect of intention on the behavior of partner farmers. The population was composed of partner farmers PT Hari Sawit Jaya located in Labuhan Batu district, North Sumatra of whom 90 farmers were sampled using the cluster proportional random sampling method. The research instrument was s questionnaire Data was analyzed by SmartPLS. Results showed that attitudes, subjective norms, behavioral control, moral norms, and knowledge had a positive effect on farmers' intention to manage sustainable oil palm and the intention had a positive effect on farmers' behavior. However, there are sustainable palm oil management behaviors in accordance with good agricultural practices that have not been carried out by partner farmers to plant oil palm on peatlands and have not used certified seeds.